(untitled) (La Rivada, 2022)
The changes brought about by globalization have generated a tendency towards the individualization of identity, which implies that people try to emancipate themselves from socially ascribed determinations, pretending to be protagonists and inventors of their own existence. This leads to the development of a fragmented personality, adaptable and without habits, which allows them to access different ephemeral fields, to enjoy their benefits in everyday life. However, these new social conditions have weakened community cohesion and harmony, as they are replaced by individualized decisions, which constantly lead to states of ambiguity and uncertainty. In this paper we analyze the category of identity in the context of an individualized society, reviewing classical theories such as those of Erikson and Merton, and contemporary positions such as those of Bauman, Beck and Martuccelli. The premise is that when individuals seek biographical solutions to structural problems, they face precarity, exclusion and overload, using individual tools that do not link up with those of other members of society.